PTH-118 Quality of Bowel Preparation for Colonoscopy: can we Learn anything from Patients' Perspectives?. (4th June 2013) - Alexander, J; Moore, S; Neild, P
Abstract : Introduction: Good quality bowel preparation (prep) with oral laxative agents is vital for accurate and safe colonoscopy. Previous work has studied associations between specific patient characteristics and inadequate bowel prep 1 . We analysed patients' perspectives of bowel prep to see if information could be gleaned to advise future patients. Methods: The study comprised 100 patients having outpatient colonoscopy at St George's Hospital in August to September 2012. In advance of the procedure, patients received two sachets of Citrafleet (to be taken 6 hours apart) and a booklet on colonoscopy & bowel prep by post. On arrival patients were asked to complete a questionnaire, including information on usual bowel habit, fluid intake, perceived efficacy of the prep and whether the first or second sachet of prep worked better. Patient demographics and medical history were collected by nursing staff at admission clerking. The Endoscopist assessed the quality of bowel prep at colonoscopy using a standard four point score (0 = good, 1 = satisfactory, 2 = poor, 3 = very poor). Results: Complete data were collected on 89 patients (age range 21–100; mean age 64): One procedure was abandoned due to failed intubation; in 10 cases the endoscopist did not comment on quality of prep. Endoscopists reported 23 cases where preparation was suboptimal, in contrast to only 5 patients (fifty seven patients felt the laxative worked very well and 38 quite well). There was a tendency towards those who thought the prep worked very well having better prep at colonoscopy, but this did not reach statistical significance (p = 0.24). Patients with depression had poorer preparation at colonoscopy (p < 0.01). Fifty seven patients felt their bowels opened most after the first sachet, 43 after the second. Those who thought the second sachet was more effective than the first had poorer bowel prep at colonoscopy (p = 0.03). Patients who reported their usual bowel habit as hard, and those with diabetes, had a tendency towards having their bowels open most after the second sachet, but neither relationship was statistically significant (p = 0.15 & 0.18 respectively). No correlations were found between patient gender, age or drinking habits and perceived quality of prep or efficacy of each sachet. Conclusion: Our results show that patients reporting more effective results after the second sachet of laxative have objectively poorer preparation at colonoscopy. We suggest that this information could be used to advise such patients that an increased fluid intake may be necessary before and after the second dose of laxative to optimise preparation. A larger study may help to identify further correlates with which we can advise our patients. Disclosure of Interest: None Declared. Reference: Ness RM, Manam R, Hoen H, Chalasani N. Predictors of inadequate bowel preparation for colonoscopy. Am J Gastroenterol. 2001 Jun; 96(6):1797–802.